(untitled) (Homoeopathy for All, 2023)
Black hairy tongue is a benign self limiting disorder characterized by hypertrophy of the filiform papillae of the tongue. In this condition a brown ish-black discoloration of the papillae occurs.The etiology is still unclear but the condition is associated with numerous predisposing conditions. Homoeopathic medicine prescribed after proper casetaking and repertor ization has shown effectiveness in treating blackhairy tongue. A 45-year old woman came with a complaint of blackish discoloration on tongue. A detailed case history was taken and after proper repertorization, the con stitutional medicine was prescribed along with repeated follow-ups were taken at an interval of 15 days. The follow-ups of the patient showed re markable improvement in her condi tion.